The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2319/121116-889.1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation of maxillary dentoalveolar changes and airway space after distalization in adults

Abstract: The application of the MCPP resulted in significant total arch distalization without a significant effect on the transverse dimensions or changes in the oropharynx airway space. The MCPP can be considered a viable treatment option for patients with Class II malocclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Thirty-three articles were then selected for full-text assessment. After the full-text appraisal, 26 articles were excluded due to the following reasons: Article in a different language [30], sample age below 16 years old [24,[31][32][33][34], Different premolar extractions [35,36], Different anchorage designs [25,[37][38][39][40][41][42][43], Different malocclusion [44], Nonretrospective studies [16,19,22,[45][46][47][48][49][50]. Six eligible retrospective study articles were selected in this systematic review [20,22,23,[51][52][53].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-three articles were then selected for full-text assessment. After the full-text appraisal, 26 articles were excluded due to the following reasons: Article in a different language [30], sample age below 16 years old [24,[31][32][33][34], Different premolar extractions [35,36], Different anchorage designs [25,[37][38][39][40][41][42][43], Different malocclusion [44], Nonretrospective studies [16,19,22,[45][46][47][48][49][50]. Six eligible retrospective study articles were selected in this systematic review [20,22,23,[51][52][53].…”
Section: Resultsmentioning
confidence: 99%
“…Following maxillary arch distalization, it has been reported that the minimum cross-sectional area of the oropharynx and airway volume were not significantly impacted by treating the included cases with premolar extraction. 31 Reports also indicate that placing mini plates on mandibular arches effectively managed class III malocclusions. 32 It has been further shown that mandibular total arch distalization and mandibular teeth retraction were also significantly achieved by placing remal plates on the retromolar fossa.…”
Section: Discussionmentioning
confidence: 99%
“…Also, several studies have showed that the size of airway space may be decreased by extraction treatment (11)(12)(13) . On the other hand, a study has showed that the airway space was not significantly affected by either extraction or nonextraction treatment of adults (14) . And also, another CBCT study has showed that there were no negative 3-dimensional (3D) long-term effects on airway space after total maxillary arch distalization using modified C-palatal plates in adolescents (15) .…”
Section: Introductionmentioning
confidence: 97%